Regulation of downstream neuronal genes by proneural transcription factors during initial neurogenesis in the vertebrate brain. Issue 1 (December 2016) - Ware, Michelle; Hamdi-Rozé, Houda; Le Friec, Julien; David, Véronique; Dupé, Valérie
Abstract Background Neurons arise in very specific regions of the neural tube, controlled by components of the Notch signalling pathway, proneural genes, and other bHLH transcription factors. How these specific neuronal areas in the brain are generated during development is just beginning to be elucidated. Notably, the critical role of proneural genes during differentiation of the neuronal populations that give rise to the early axon scaffold in the developing brain is not understood. The regulation of their downstream effectors remains poorly defined. Results This study provides the first overview of the spatiotemporal expression of proneural genes in the neuronal populations of the early axon scaffold in both chick and mouse. Overexpression studies and mutant mice have identified a number of specific neuronal genes that are targets of proneural transcription factors in these neuronal populations. Conclusion Together, these results improve our understanding of the molecular mechanisms involved in differentiation of the first neuronal populations in the brain.